Modernization of the public accounting system in Algeria in accordance with International Public Sector Accounting Standards (IPSAS) - Nesrine, Beladjal; Salima, Ghorzi (International journal of economic perspectives, 2024)
The objective of this study is to identify the extent to which an appropriate environment can be adapted to IPSAS by identifying the various motives that led to the reform and study of the modernization of the public accounting system, in addition to the efforts of the most important arrangements for this reform, It was concluded that this project is still being studied and developed due to several difficulties faced by the application. The entry into force of the new accounting plan requires, first and foremost, the final implementation of the project 'Restructuring Implementation Procedures'. Public expenditure 'which allows for the accounting restriction of proven rights related to real-time expenditures for compliance, and requires a developed automated information system. This study explores the modernization of the public accounting system in Algeria in alignment with International Public Sector Accounting Standards (IPSAS), highlighting the motives for reform, efforts towards modernization, and challenges faced in implementation